PENGARUH PERSEPSI HARGA, PROMOSI DUNIA MAYA DAN CYBERCRIME TERHADAP MINAT BELI (INDOMARET KECAMATAN GADING CEMPAKA KOTA BENGKULU) - M.Tidi Battiar; Subandrio Subandrio (UM. Bengkulu, 2022)
This study aims to determine the variables that affect buying interest in Indomaret kec. Gading Cempaka, Bengkulu City, either partially or simultaneously. There are several variables that will be discussed in this study, including price perception (X1), cyber promotion (X2), and cyber crime (X3). In this study the authors used the data collection method by means of observation, distributing questionnaires or questionnaires. The object in this study were consumers of Indomaret Kec. Gading Cempaka, Bengkulu City with a total of 90 respondents. And the determination of the sample used in this study used accidental sampling technique, namely taking respondents as a sample based on chance, that is, anyone who happens to meet the researcher can be used as a sample. In this study, the authors used several data analysis techniques, namely instrument test, classical assumption test, respondent response analysis, classical assumption test, multiple linear regression analysis, determinant coefficient, and hypothesis testing. From the results of the tests that have been carried out, it can be concluded that Price Perception (X_1), Virtual World Promotion (X_2) and Cyber Crime (X3) on the dependent variable Buy Interest (Y), this can be seen in the F test which states the value of F_count> Ftable, namely (127,964> 3,102) and (sig α = 0.000 <0.050), it can be concluded that H_3 is accepted, meaning that simultaneously Knowledge (X_1), Product (X_2) and Promotion (X3) variables have a significant effect on Purchase Intention (Y ) in Indomaret Kec Gading Cempaka, Bengkulu City. Keywords: Price Perception, Cyber Promotion, Cyber Crime, and Buying Interest.